Determination of mangiferin using carbon paste electrode modified with ionic liquid and NiFe2O4 nanoparticles - Hadi Beitollahi; Shohreh Jahani (شیمی کاربردی روز, 2019)
A highly sensitive electrochemical sensor was fabricated based on ionic liquid and NiFe2O4 nanoparticles modified carbon paste electrode for determination of mangiferin. The modified electrode exhibited excellent electrocatalytic activity towards the oxidations mangiferin in phosphate buffer solution (pH 7.0). Cyclic voltammetry (CV), chronoamperometry (CHA) and differential pulse voltammetry (DPV) were used to investigate the electrochemical reaction of mangiferin at the modified electrode. It dramatically enhanced mangiferin oxidation current and shifted its potential towards less positive potential when compared to bare CPE. The peak current vs. mangiferin concentration diagram was found to be linear in range of 0.1 to 500.0 μM with the respective slope of 0.0576 μA μM-1. The detection limit obtained by DPV was 0.09 μM (S/N = 3). The proposed sensor was proved to be applicable for the determination of the mangiferin in urine samples.